Neurostimulation technology for the treatment of chronic pain: a focus on spinal cord stimulation. (March 2007) - Foletti, Antonio; Durrer, Anne; Buchser, Eric
Over the past 40 years we have seen how electrical stimulation for the relief of pain has progressed from an experimental treatment based upon a clinical theory to being on the threshold of becoming a standard of medical practice. While tens of thousands of devices are implanted every year, the mechanism of action still evades complete understanding. Nevertheless, technological improvements have been considerable and the current neuromodulation devices are both extremely sophisticated and reliable. Unlike most conventional treatments, neurostimulation cannot be restricted to one speciality as its clinical applications ignore the boundaries of medical specialities. Conditions such as neuropathic pain in the back and the leg, complex regional pain syndrome, ischemic pain due to peripheral vascular disease and coronary artery disease are likely to respond to spinal cord stimulation. Even though the evidence for efficacy remains unsatisfactory, the stimulation of the dorsal column has been remarkably successful in relieving pain and improving function in patients who have failed conventional management. The development, the technicalities and the most important clinical applications of spinal cord stimulation are reviewed here.